Rails on Windows. - Hibbs, Curt (O'Reilly Media, 2009)
It's no secret that the entire Ruby onRails core team uses OS X as their preferreddevelopment environment. Becauseof this, it is very easy to findauthoritative information on the webabout using Rails on OS X. But the truthis that Windows developers using Railsprobably outnumber those using otherplatforms. A Windows development environmentcan be just as productive asany other platform. This is a guide to developing with Rubyon Rails under Windows. It won't teachyou how to write Ruby on Rails web applications, but it will show you what toolsto use and how to set them up to createa complete Rails development environment.